2007
DOI: 10.1021/ol0622054
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Cyclopropylamines Starting from N-Sulfinyl α-Chloro Ketimines

Abstract: Treatment of novel chiral N-sulfinyl alpha-chloro ketimines with Grignard reagents resulted in the synthesis of chiral N-(1-substituted cyclopropyl)-tert-butanesulfinamides in acceptable to good yields and diastereoselectivity via 1,3-dehydrohalogenation and subsequent addition of the Grignard reagent to the intermediate cyclopropylideneamine. Only in the case of allylmagnesium chloride did the reaction lead to aziridines in high yield. Further deprotection toward N-unprotected 1-substituted cyclopropylamines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…De Kimpe and co-workers also reported the synthesis of N - tert -butanesulfinyl aziridines via the addition of allyl Grignard reagent to α-chloro N - tert -butanesulfinyl ketimines 1104a − c (eq ) . The aziridine products 1105a − c were obtained in good yields (65−95%) and with high diastereoselectivities (93:7 to >95:5).…”
Section: Synthesis Of Aziridinesmentioning
confidence: 99%
See 2 more Smart Citations
“…De Kimpe and co-workers also reported the synthesis of N - tert -butanesulfinyl aziridines via the addition of allyl Grignard reagent to α-chloro N - tert -butanesulfinyl ketimines 1104a − c (eq ) . The aziridine products 1105a − c were obtained in good yields (65−95%) and with high diastereoselectivities (93:7 to >95:5).…”
Section: Synthesis Of Aziridinesmentioning
confidence: 99%
“…A synthesis of cyclopropylamines via a proposed Favorskii-type rearrangement upon reaction of Grignard reagents with α-chloro N - tert -butanesulfinyl ketimines 329 was reported by De Kimpe and co-workers (Scheme ) . Optimization of the reaction conditions revealed that addition of 2.2 equiv of the Grignard reagent to the ketimine at −78 °C followed by subsequent warming to −40 °C provided the highest yields and diastereoselectivities of this interesting class of compounds.…”
Section: Synthesis Of αα-Dibranched Amines (Tertiary Carbinamines)mentioning
confidence: 99%
See 1 more Smart Citation
“…They utilised a chiral N-sulfinyl a-chloro ketimine 23 as the starting material. Reduction of 23 with borohydride reagents gave the corresponding aziridines, 51 and reaction of 23 with Grignard reagents gave either the corresponding aziridine or aminocyclopropane, 52 depending on the conditions (Scheme 20). Sulfinyl deprotection was achieved with dry hydrochloric acid in 1,4-dioxane, giving the corresponding hydrochloride salts with retention of configuration.…”
Section: Organosulfur Compounds As Intermediates or Catalystsmentioning
confidence: 99%
“…[114][115][116][117][118][119][120][121] So far, such imines have been intensively used in asymmetric synthesis. [122][123][124][125][126][127][128][129][130][131][132][133][134][135] The trans-acetylenic aziridines (AE)-33 are then formed as major isomers (trans : cis 4 91 : 9). Moreover, in all cases only one trans-aziridine (dr 4 98 : 2) was formed suggesting that the tBS-group has fully played its role of a chiral directing group.…”
Section: Stereoselective Synthesis Of Enantioenriched Transacetylenic...mentioning
confidence: 99%